Television Consumption Patterns among Sabah’s Kadazan-Dusun Youth in the Era of Digital Society - Cyril Modili; Haryati Abd Karim; Juliana Abd Wahab (Prademic Press, 2022)
The purpose of this article is to gain insight into the impact of digital technologies' emergence on the television consumption patterns among Kadazan-Dusun youths in Sabah in the era of digital society. An online survey was conducted using a Google form, and SPSS was utilised to analyse the results. The survey sampled 411 respondents aged 18 to 25 years old who resided in four major areas: Kota Kinabalu, Penampang, Ranau, and Keningau. As shown in the research, television consumption patterns among Kadazan-Dusun youth in Sabah are changing in lockstep with the changing television environment, which now includes multi-platform channels. The respondents place a higher premium on the use of alternative television platforms to receive television content than on traditional television. Additionally, technological advancements make it easier for viewers to get their favourite shows regardless of where they are. Thus, the data demonstrate that the television-or alternative television-consumption patterns of Kadazan-Dusun adolescents in Sabah are more likely to be motivated by self-preference and personal taste nowadays.